2004
DOI: 10.7202/008490ar
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution profile of Colorado potato beetle [Coleoptera: Chrysomelidae] in flight above host, resistant host and non-host fields

Abstract: We evaluated the vertical stratification of Colorado potato beetle (Leptinotarsa decemlineata) (CPB) populations in flight above fields of conventional potato, an insect resistant potato field expressing genes for Bacillus thuringiensis tenebrionis (Btt) toxins and a non-host clover field. Flight interception traps at 0 - 1.2, 1.2 - 2.4 and 2.4 - 3.6 m above ground were used to determine the vertical profiles of the aerial population over each crop for a growing season. The distribution of overwintered and sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Spencer et al 4 determined that 85–90% of western corn rootworm movements are local and of short distance (4.6–9.1 m day −1 ). The relationship between the height of flight at take‐off and the distance flown by adult Colorado potato beetle was studied5 by visually observing individuals leaving a release point at the centre of a 10 m radius potato field arena. Likewise, behavioural studies of adult plum curculios labelled with the radioisotope Zn 65 allowed a better understanding of its field behaviour,6 and, ultimately, the results were used to design optimal management strategies 7…”
Section: Introductionmentioning
confidence: 99%
“…Spencer et al 4 determined that 85–90% of western corn rootworm movements are local and of short distance (4.6–9.1 m day −1 ). The relationship between the height of flight at take‐off and the distance flown by adult Colorado potato beetle was studied5 by visually observing individuals leaving a release point at the centre of a 10 m radius potato field arena. Likewise, behavioural studies of adult plum curculios labelled with the radioisotope Zn 65 allowed a better understanding of its field behaviour,6 and, ultimately, the results were used to design optimal management strategies 7…”
Section: Introductionmentioning
confidence: 99%
“…The relative quality or plant phenology of habitats (Mbungu & Boiteau, ) could generate different CPB dispersal rates. MacQuarrie & Boiteau () observed more flights from summer CPB exposed to poor host than to conventional potato. Each seasonal beetle type is likely to have evolved different dispersal strategies (Jermy et al., ; Weber & Ferro, ).…”
Section: Introductionmentioning
confidence: 99%
“…Each seasonal beetle type is likely to have evolved different dispersal strategies (Jermy et al., ; Weber & Ferro, ). MacQuarrie & Boiteau () recorded summer CPB flights, but essentially no overwintered beetle flights, in a pasture. They suggested that overwintered CPB limit their dispersal to within host fields or to higher altitude across non‐host fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations